Cradle Cap in Association with Scalp Hygiene and Traditional Practices: A Case Report - Debby Kurniawan Chandra Saputra; Putu Dyah Ayu Saraswati (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Cradle cap, or infantile seborrheic dermatitis, is a common benign inflammatory condition in infants that mainly affects the scalp. It is often misattributed to poor hygiene, although its etiology is multifactorial, involving sebaceous gland activity, microbial colonization, and immune immaturity. Scalp care practices and traditional treatments may influence severity and duration. We report a case of a 4-month-old male infant with erythematous plaques and thick yellow scales on the scalp for seven days after repeated application of traditional oil without regular cleansing. The infant showed normal growth and no systemic symptoms. Diagnosis was made clinically. Management consisted of parental education, discontinuation of oil use, daily gentle cleansing with baby shampoo, and topical hydrocortisone 1% combined with ketoconazole 2% twice daily. After two weeks, lesions resolved completely without recurrence or side effects. This case emphasizes the importance of proper scalp hygiene, caregiver education, and appropriate topical therapy. Keywords: Cradle Cap, Infantile Seborrheic Dermatitis, Scalp Hygiene, Traditional Practices.